Do College Anti-Plagiarism/Cheating Policies Have Teeth in the Age of AI? Evidence from the United States - Rajeev K. Goel; Michael A. Nelson (Center for Economic Studies and ifo Institute (CESifo), 2023)
The advent of the internet, and more recently of artificial intelligence (AI), has challenged academic and other institutions to ensure ethical practices and reward/promote true merit. The borderless and relatively anonymous nature of the internet creates policing challenges, leading to the abuse of established rules and standards. In the context of academia, this impacts the size and scope of resources to facilitate/check plagiarism and cheating, both from the demand and supply sides. Adding some formal insights into the current topic of fundamental importance to maintaining academic integrity, this paper examines the association of anti-plagiarism/anti-cheating policies with resources that facilitate such behavior (legal or otherwise). Using unique internet search indices of the policies and resources, we find that the two are positively associated – the associated resources ratchet up with the policies. This association is robust to different modeling formulations, including when the internet policies include course syllabi. The findings reinforce the view that policies to check plagiarism and cheating are likely to lack teeth and may be a step behind the resources that facilitate unethical behaviour.
Keywords: A20; I23; L86; 330; AI; artificial intelligence; plagiarism; cheating; internet; universities; colleges; United States